Analisis Faktor Persepsi pada Atribut Produk, Personal, Sosial, dan Budaya terhadap Keputusan Pembelian (Studi Kasus Kuliner Kota Kuningan) - Rahadian Muslim; Edi Setiawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the factors influencing tourists’ purchasing decisions regarding the traditional culinary product Tape Ketan Pamela in Kuningan Regency. The factors examined include cultural, social, and personal factors, as well as product attributes consisting of product quality, cleanliness, price perception, and promotion. This research employed a quantitative approach using logistic regression analysis. Data were collected through questionnaires distributed to 150 tourist respondents who visited Kuningan Regency and were familiar with or had purchased Tape Ketan Pamela. The results of the logistic regression analysis indicate that several variables significantly influence tourists’ purchasing decisions. The variables of visit purpose, age, and product attributes, particularly perceived product cleanliness are significant predictors of purchasing decisions. Among these variables, visit purpose shows the highest odds ratio, indicating that it is the most dominant factor influencing the likelihood of purchasing the product. Meanwhile, nationality does not have a significant effect on purchasing decisions. This study contributes to the literature on consumer behavior in the context of local culinary tourism and provides practical implications for business owners in developing data-driven marketing strategies based on tourist characteristics and product attributes. Future studies are recommended to include additional variables such as brand image, culinary experience, and customer loyalty to enhance the explanatory power of the model.